(untitled) (Konturen, 2008)
Renaissance perspective constructs objective reality from the viewpoint of a sovereign subject. The border protecting the sovereignty of this subject is sometimes crossed, in the Baroque, by means of the subject’s sudden awareness of the humanity of the other person and of our inescapable responsibility for that unique and irreplaceable other. With examples from music, painting, and literature, I discuss what I call “eruptions of the ethical Baroque.” These eruptions trouble the serenity of the arts and haunt us: one such eruption reveals, to the Christian warrior-crusader Tancredi, the face of the apparently Muslim female warrior Clorinda, in Monteverdi’s "Combattimento di Tancredi e Clorinda"(1624); another reveals, to Abraham—in Rembrandt’s 1635 painting of "The Sacrifice of Isaac"— the face of his son Isaac and then suddenly interrupts what appeared to have been an imminent murder; another forces us to encounter, in Shakespeare’s disruptively sober prose, Shylock’s Jewish eyes; yet another, in Paul Celan’s arguably modern Baroque poem "Tenebrae", interrupts—but too late, tragically—the profoundly enchanting pathos of François Couperin’s high Baroque choral masterpiece, "Leçons de ténèbres", which inspired Celan’s poem.